Ocorrência de patógenos de origem bacteriana e viral e marcadores de virulência de Escherichia coli e Rhodococcus equi isolados das fezes de aves silvestres de cativiero da fauna brasileira - Morais, Amanda Bonalume Cordeiro de [UNESP] (2014)
The present study investigated the occurrence of Escherichia coli, Rhodococcus equi, Salmonella sp., Coronavirus and Rotavirus in the feces of Passeriformes and psittaciformes belonging to Brazilian wildlife, from 29 different species, without enteric signs. Virulence markers were also investigated in strains of E. coli (cnf1, hlyA, papC, papGI, papGII, papGIII, fimH, afa, sfa, iucD, usp, vt1, vt2, eae, k88) and R. equi (vapA and vapB genes). The birds used in the study came from the Centro de Medicina e Pesquisa em Animais Silvestres (CEMPAS) FMVZ - UNESP / Botucatu, SP, Parque Zoológico Municipal Quinzinho de Barros (PZMQB) Sorocaba, SP and private breeders with birds recorded in Instituto Brasileiro do Meio Ambiente e dos Recursos Renováveis (IBAMA) from Botucatu region, SP. Of the total 152 fecal samples evaluated were isolated 46 (30.26%) strains of E. coli. From these, 37 (80%) were from psittaciformes samples and 9 (20%) of Passeriformes. There was a statistical difference (p <0.05) between groups with greater isolation of E. coli in psittaciformes. Among the virulence markers of E. coli were detected the genes fimH (58,69%) and eae (4,34%). Were isolated 2 (1.32%) R. equi strains, all from psittaciformes. Among these R. equi isolates any vapA and vapB genes associated with virulence were founded. Genetic material of bovine Rotavirus was found in three (1.97%) psittaciformes samples. Salmonella sp. and Coronavírus weren’t identified in any of the sampled birds. The presence of E. coli, R. equi and Rotavirus in fecal samples of wild birds without enteric signs from Brazil wildlife, reinforces the potential of these birds as a reservoirs of pathogens of enteric elimination for humans, due to the presence of these animals in the domestic and peridomestic, environment of human